2014
DOI: 10.1590/s1517-83822014000100020
|View full text |Cite
|
Sign up to set email alerts
|

Protozoans bacterivory in a subtropical environment during a dry/cold and a rainy/warm season

Abstract: In aquatic ecosystems, bacteria are controlled by several organisms in the food chain, such as protozoa, that use them as food source. This study aimed to quantify the ingestion and clearance rates of bacteria by ciliates and heterotrophic nanoflagellates (HNF) in a subtropical freshwater reservoir (Monjolinho reservoir - São Carlos - Brazil) during one year period, in order to verify their importance as consumers and controllers of bacteria in two seasons, a dry/cold and a rainy/warm one. For this purpose, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For instance, it has been shown that Microcystis, which accumulates in spring, is critical for the microbial community structure in aquatic ecosystems ( Zuo et al, 2021 ). The eukaryotic taxon Tintinnidium, which feeds on most bacteria, is an important biotic factor in regulating the bacterial community in aquatic ecosystems ( Hisatugo et al, 2014 ). The prokaryotic taxon HgcI clade that was found in summer could improve water quality due to its participation in N fixation and denitrification ( Ruprecht et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that Microcystis, which accumulates in spring, is critical for the microbial community structure in aquatic ecosystems ( Zuo et al, 2021 ). The eukaryotic taxon Tintinnidium, which feeds on most bacteria, is an important biotic factor in regulating the bacterial community in aquatic ecosystems ( Hisatugo et al, 2014 ). The prokaryotic taxon HgcI clade that was found in summer could improve water quality due to its participation in N fixation and denitrification ( Ruprecht et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a correlation between class 1 and 2 ciliates and temperature and dissolved oxygen highlights the presence of organic contamination in these sites, as high bacterial population densities are found in organically polluted environments, which contributes to an increase in temperature and a decrease in dissolved oxygen from the water, and the stimulation of the growth of the populations of bacterivorous ciliates. Recent studies (Hisatugo et al, 2014;Mansano et al, 2014) have demonstrated that heterototrophic ciliated protozoa and nano agellates present high rates of bacterial ingestion, representing an important bacterial control in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a correlation between class 1 and 2 ciliates and temperature and dissolved oxygen highlights the presence of organic contamination in these sites, as high bacterial population densities are found in organically polluted environments, which contributes to an increase in temperature and a decrease in dissolved oxygen from the water, and the stimulation of the growth of the populations of bacterivorous ciliates. Recent studies (Hisatugo et al, 2014;Mansano et al, 2014) have demonstrated that heterototrophic ciliated protozoa and nano agellates present high rates of bacterial ingestion, representing an important bacterial control in the environment.…”
Section: Discussionmentioning
confidence: 99%